2013
DOI: 10.1111/medu.12154
|View full text |Cite
|
Sign up to set email alerts
|

Curricular transformations in medical school: an exploration of the promotion of change in Brazil

Abstract: The PROMED initiative provided considerable support for implementing and consolidating curricular reforms that placed greater emphasis on the needs of society and the health care system. The different trends observed revealed the complexity behind curricular transformation and highlighted the need for the collective construction of curricula with the participation of all groups involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…Given that the universal Brazilian healthcare system emphasizes preventive medicine, the low interest of students in pursuing primary care specialties is a major national issue. This situation is aggravated by the lack of physicians (national mean of 1.8 professionals per 1000 habitants) and an unequal geographic distribution of this workforce [ 23 , 36 ]. Importantly, a survey of medical residents in the United States reported that internships significantly influence the choice of primary care [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the universal Brazilian healthcare system emphasizes preventive medicine, the low interest of students in pursuing primary care specialties is a major national issue. This situation is aggravated by the lack of physicians (national mean of 1.8 professionals per 1000 habitants) and an unequal geographic distribution of this workforce [ 23 , 36 ]. Importantly, a survey of medical residents in the United States reported that internships significantly influence the choice of primary care [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, general practice (i.e., family medicine) is the third most popular career choice in junior doctors [ 20 ]. In contrast, the situation in Brazil is marked by a low interest in general practice (including primary care), which impairs the medical needs for social programs from the universal Brazilian healthcare system [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado reflete o movimento observado durante a realização do Promed em que muitos cursos de Medicina propuseram a inserção dos estudantes em cenários reais de prática desde o início dos cursos como uma das estratégias do vetor "mudança de cenários de prática" 10 .…”
Section: Resultsunclassified
“…Entretanto, na busca pela adequação da formação profissional, essas escolas se deparam com inúmeros obstáculos que as impedem de avançar nesse processo. Uma avaliação de desempenho do Promed nas 19 escolas participantes apontou dificuldades na integração ensino-serviço, baixa produção de conhecimentos voltadosàs necessidades do SUS e estrangulamentos na oferta de pós-graduação e educação permanente 10 . Esse estrangulamento do processo de mudanças pode ser reflexo da hegemonia de grupos tradicionais de pesquisa mais voltados para o desenvolvimento de linhas de estudo das especialidades médicas 11 .…”
Section: Introductionunclassified
“…Even though universities spend a great amount of resources planning and implementing educational programs, a major issue is the intricate problem of evaluating the impact of curricula in students' academic performance [3][4][5]. It is not straightforward to identify the individual components of a major curricular change and their effects on the plethora of outcome variables, indicators of teacher performance and student learning, since there are many interlinked variables that can influence the main outcomes [3,4,6].…”
Section: Introductionmentioning
confidence: 99%